The Influence of Corporate Governance and Accounting Conservatism on Tax Aggressiveness in Automotive and Component Sub-Sector Companies - Thea Juliane Kristy; Linda Santioso (Economic Reviews Journal, 2024)
This study aims to obtain empirical evidence regarding the impact of corporate governance, projected through independent commissioners and audit committees, as well as accounting conservatism as independent variables, on tax aggressiveness as the dependent variable in automotive and component subsector companies listed on the Indonesia Stock Exchange (IDX) during the research period from 2018 to 2022. In this study, independent commissioners are measured by the ratio of the number of independent commissioners to the total board of commissioners. The audit committee is measured by the number of current audit committee members in the company. Accounting conservatism is measured by summing operating income with depreciation of fixed assets, then subtracting the net cash flow from operating activities, and dividing by the total assets of the company, with the result then multiplied by -1. Tax aggressiveness is measured by the Effective Tax Rate (ETR), calculated by dividing income tax expense by pre-tax income of the company. The sample size for this study is 11 companies, where the sample data were selected using purposive sampling. The data are analyzed using a multiple linear regression model processed with IBM SPSS Statistics version 23. The results of this study indicate that independent commissioners have a significant negative effect on tax aggressiveness, while the audit committee and accounting conservatism do not have a significant effect on tax aggressiveness.